2000
DOI: 10.1175/1520-0426(2000)017<0017:swmoct>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Scintillometer Wind Measurements over Complex Terrain

Abstract: Several large-aperture scintillometers were built at the Paul Scherrer Institute with the aim to measure wind over complex terrain. A prototype instrument was tested over flat ground, and the performance of six analyzing techniques was evaluated by comparing them with conventional anemometers. Next, a set of five improved scintillometers was used in an experiment over complex terrain. This experiment represents a unique opportunity for evaluating scintillometer performance by comparing their results to sodar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…When crosswind speeds are low, this assumption is less justified and eddies decay as they are slowly blown through the beam. Correlation between the received scintillation pattern from one sample to the next is reduced compared to higher crosswind cases (Poggio et al, 2000). Correlation between the scintillation signals of the BLS and MWS will likely show greater variation too, depending on how the decay of eddies affects each beam, which would result in variability in C n1n2 that propagates through to r T q_bc .…”
Section: Temperature-humidity Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…When crosswind speeds are low, this assumption is less justified and eddies decay as they are slowly blown through the beam. Correlation between the received scintillation pattern from one sample to the next is reduced compared to higher crosswind cases (Poggio et al, 2000). Correlation between the scintillation signals of the BLS and MWS will likely show greater variation too, depending on how the decay of eddies affects each beam, which would result in variability in C n1n2 that propagates through to r T q_bc .…”
Section: Temperature-humidity Correlationmentioning
confidence: 99%
“…Scintillometer measurements have been carried out at sites of varying complexity, from tests of the technique under simple conditions (Hill and Ochs, 1978;De Bruin et al, 1993) to studies investigating the complications of non-ideal terrain, including heterogeneous land cover (Beyrich et al, 2002;Meijninger et al, 2002aMeijninger et al, , 2006Ezzahar et al, 2007) and complex topography (Poggio et al, 2000;Evans, 2009;Evans et al, 2012). On the whole, these studies have shown that scintillometers installed above or close to the blending height can provide valuable area-averaged fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Lawrence et al 1972;Wang et al 1981;Poggio et al 2000) have already shown that a scintillometer is able to obtain the crosswind correctly. The crosswind (U ⊥ ) is the wind component perpendicular to a path.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the validation studies for a scintillometer measuring U ⊥ have taken place over flat grassland sites (e.g. Poggio et al 2000;van Dinther et al 2013;van Dinther and Hartogensis 2014), over which U ⊥ can be assumed constant along the scintillometer path. Around airport runways, the scintillometer signal will be affected by turbulence induced by aircraft, however.…”
Section: Introductionmentioning
confidence: 99%
“…The Flevoland experiment in The Netherlands in 1998 (Meijninger et al 2002), as well as the LITFASS campaigns in 1998LITFASS campaigns in , 2003LITFASS campaigns in and 2009, took place over a variety of different crop types and although fairly flat the land surface is described as heterogeneous (Meijninger et al 2006). The study of Poggio et al (2000) in the Mesolcina Valley in the Alps had the aim of testing scintillometry over complex terrain. Similarly, Evans (2009) analyzes scintillometry data collected over topographically variable chalk downland in southern England.…”
mentioning
confidence: 99%